Luminescent organoboron ladder compounds via directed electrophilic aromatic C–H borylation. Issue 11 (5th February 2016) - Yusuf, Mayyadah; Liu, Kanglei; Guo, Fang; Lalancette, Roger A.; Jäkle, Frieder
Abstract : Regioselective electrophilic borylation of a pyridyl-flanked fluorene provides highly luminescent, air-stable boron-bridged ladder species. Abstract : Luminescent B–N containing conjugated ladder compounds are prepared by directed electrophilic aromatic substitution. Negishi cross-coupling reaction of 2, 7-dibromo-9, 9-dihexylfluorene with 6-methylpyridin-2-yl(pivaloyloxy)zinc furnishes the dipyridylfluorene precursor (1 ) in 44% yield. Compound1 is then subjected to electrophilic borylation with BBr3 in the presence of iPr2 NEt as a bulky base to give the tetra-coordinate ladder-type organoboron species2-Br . Arylation of2-Br is accomplished by addition of Ph2 Zn or C6 F5 Cu in toluene furnishing the targeted bis(pentafluorophenyl)borane and diphenylborane species2-Ar (Ar = Ph, C6 F5 ) in 53 and 44% yield respectively. The products show a strong blue emission and undergo multi-step reversible reduction and oxidation processes. The effect of fluorination of the pendant aryl groups on the electronic structure is further examined by DFT methods.